Correlation between the performance of solid masonry prisms and wallettes under compression. (March 2019) - Thamboo, Julian Ajith; Dhanasekar, Manicka
Abstract: Strength and deformation characteristics of masonry under uniaxial compression are researched over decades using prisms and wallettes; however, correlation between these two common test methods is not firmly established. Masonry design standards provide expressions and tabulated data for the determination of the compression characteristics from either the prism or the wallette tests. Subsequently researchers compared the standards and made conclusions on their respective conservativism or otherwise, without any regard to the way these provisions have been developed for these design standards. Hence an attempt was made to correlate the behaviour of the solid masonry prism to the wallette compressive behaviour. Fifty prisms and forty wallettes were constructed and tested using five different types of units and two mortar mixes. The test results have revealed that the prism tests consistently provide higher compressive strength than that of the corresponding wallettes specimens. A linear relationship between the compressive strengths of the prisms and the wallettes has been found appropriate. For the deformation characteristics of masonry, simplified analytical model is proposed to correlate the test data from the prisms and the wallettes. Highlights: Wallettes and prisms from same brick – mortar group constructed and tested. Conservative compressive strength of masonry is obtained from wallette tests. Mean strength of wallette is linearly regressed to mean prism strength. Deformation characteristics of wallettes and prisms reported. An analytical model stress-strain relation for prisms and wallettes reported.